Respons Pertumbuhan dan Produksi Kailan (Brassica Oleraceae L.) pada Pemberian Berbagai Dosis Pupuk Organik Cair Paitan (Tithonia Diversifolia (Hemsl.) Gray ) - Posma Sinaga; Meiriani Meiriani; Yaya Hasanah Yaya Hasanah (Jurnal Agroekoteknologi, 2014)
The objective of the research was to determine the growth and production of mustard withapplication of liquid organic fertilizer from paitan . Paitan has the potencial as the nutrition adderfor plant because it can be rapidly decomposed and has many nutrients. Therefore, the applicationof liquid organic fertilizer from paitan is hoped to increase the growth and yield of mustard. Thisresearch conducted in Screen House, Faculty of Agriculture, University of Sumatera Utara, Medanon November 2013 to January 2014. The research used non-factorial randomized block designnamely of liquid organic fertilizer treatment (4, 8,12,7, 14 and 21 ml/plant/aplication). Variableobserved were leaf greeness scale, net assimilation rate, relative growth rate and fresh weight perplant. The result showed that the application of liquid organic fertilizer from Tithonia diversifoliasignificantly did not effect the growth and production of mustard. The best result showed by giving8 ml/plant/application liquid organic fertilizer.Keywords : liquid organik fertilizer, mustard, paitan